Factors enabling organisational agility within the South African coal mining industry - Khutama, Lethabo Mokgohlwa Euphemia (My University, 2017)
The South African coal mining industry is dynamic, unpredictable, complex and competitive because of the many challenges that it faces. These problems include the fact that the demand for coal on a global scale is declining and the resources of coal are becoming scarce and difficult to mine. Labour unrest is a common practice in the country, and the environmental challenges associated with the mining of coal is what makes this industry so complicated. These are some of the problems that would drive the need for organisations operating in this industry to seek ways of staying ahead and one of those being agility. The question asked was, is it possible for organisations operating in this industry to remain agile in the midst of the challenges that they face? As such, the aim of the research was to determine the factors enabling organisational agility, which South African coal mining companies could adopt. The study, however, did not seek to determine which of these factors the coal mining companies should choose but rather gave an overview and conclusion on the results obtained. The primary method used in this research study to resolve the research question was a desktop methodology. This method was used to find these factors in the literature and then use a semi-quantitative method called fuzzy cognitive mapping (FCM) as well as a simulation to determine which of these factors from the literature enable organisational agility. The map consists of nodes where causal links between each node were identified. The strength of the connections was determined by the values between [-1; 1]. Each node was defined together with the steady state definitions as well as the descriptions of the positive or negative links between the nodes. FCMs are easy to use, and the fact that they are utilised for variables that cannot be defined clearly is what makes them so attractive. Although they are easy to apply and simple to understand, the boundary of the study should be clearly set so that it is not too broad. The focus was only on the seven key enablers amongst the many which were determined from the literature as enabling organisational agility. The rest of the factors were used rather as inputs to draw the map. The map could have iii been drawn anyhow, and the outcome could have been different to what the study indicated. The fact that the result of the map could have been different is what introduces bias into the map because the drawing of the map is limited or dependent upon the knowledge of the person drawing the map. As such, it is recommended that the map be evaluated by the industry expert/s to assess and make recommendations where necessary. The map was sent to the industry expert to evaluate, and it was found that the factors, which have been determined, were researched thoroughly. The key findings from the study were that there are seven key enablers influencing other related variables, which enable organisational agility, and these are employee empowerment/ autonomy, leadership, active opportunity seeking/ alertness, team working/ team building, scanning the environment, continuous and fast learning organisation and information systems. It was further found that out of the seven key enablers, information systems are the most important key enabler in an organisation and this correlates well with what is said in the literature. The key message is that organisational agility is a process, and an organisation must evaluate carefully and compare the benefits with the disadvantages before trying to become agile. It is easier for a smaller organisation to become agile than a well-established organisation like in the coal mining industry. However, should there be a pressing need for an organisation to become agile, the key factors have been determined that can be considered by any organisation in this industry.
MBA(Thesis)
MBA(Thesis)
Keywords: Coal mines and mining -- South Africa.Information technology -- South Africa.Organizational learning -- South Africa.